Declining trend in transmitted drug resistance detected in a prospective cohort study of acute HIV infection in Bangkok, Thailand. Issue 1 (31st October 2016) - Colby, Donn J; Crowell, Trevor A; Sirivichayakul, Sunee; Pinyakorn, Suteeraporn; Kroon, Eugene; Benjapornpong, Khunthalee; Intasan, Jintana; Trichavaroj, Rapee; Tovanabutra, Sodsai; Robb, Merlin; Phanuphak, Praphan; Ananworanich, Jintanat; et al.
Abstract : Introduction: As availability of antiretroviral therapy expands in developing countries, the risk for transmission of drug‐resistant HIV also increases. Patients with acute HIV infection (AHI) provide an opportunity for real‐time monitoring of transmitted drug resistance (TDR). SEARCH 010/RV 254 study is a prospective, longitudinal study of AHI. This analysis was performed to characterize changes in TDR over time in persons enrolled in the AHI cohort. Methods: Genotype testing for TDR mutations was performed on 229 subjects enrolled from 2009 to 2014. Results: The cohort was predominantly male (95%) and men who have sex with men (92%). TDR prevalence was 7.0%, declining from 12.5% in 2009–2010 to 4.8% in 2013–2014 ( p =0.08). By drug class, resistance prevalence was 3.6% for proteases inhibitors, 2.6% for nucleoside/nucleotide reverse transcriptase inhibitors and 2.2% for non‐nucleoside reverse transcriptase inhibitors. The greatest decline in prevalence was seen in the non‐nucleoside reverses transcriptase inhibitors, from 9.4% in 2009–2010 to 0.7% in 2013–2014 ( p =0.005). Conclusions: TDR appears to be declining among individuals with AHI in Bangkok and in 2013 to 2014 met the World Health Organization definition for low prevalence. Continued surveillance is necessary to determine if this trend persists.